Thermal design of linear induction and synchronous motor for electromagnetic launch of civil aircraft - Bertola, Luca; Cox, Tom; Wheeler, Patrick; Garvey, Seamus D.; Morvan, Herve (Institute of Electrical and Electronics Engineers, 2017)
The engine size of modern passenger transport aircraft is principally determined by take-off conditions, since initial acceleration requires maximum engine power. An elec¬tromagnetic launch (EML) system could provide some or all of the energy required at takeoff so that the aircraft engine power requirement and fuel consumption may be significantly reduced. So far, EML for aircraft has been adopted only for military applications to replace steam catapults on the deck of aircraft carriers. This paper will describe the potential application of EML to propel civil aircraft on the runways of modern air¬ports. A comparison of synchronous and asynchronous electrical motor systems designed to launch an A320-200 sized aircraft is presented. The paper also describes a solution of the transient heat transfer problem applied to the conductive components of EML systems.